Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

-1 (1 + 7x) - 6(-7 -x) = 36

Sagot :

Answer: x = 5

Step-by-step explanation:

    If you need to solve for x,

Given:

-1 (1 + 7x) - 6(-7 -x) = 36

Distribute:

-1 - 7x + 42 + 6x = 36

Combine like terms:

- x + 41 = 36

Subtract 41 from both sides of the equation:

- x = -5

Divide both sides by -1:

x = 5